A maximum entropy approach to the study of residue‐specific backbone angle distributions in α‐synuclein, an intrinsically disordered protein. (22nd July 2014) - Mantsyzov, Alexey B.; Maltsev, Alexander S.; Ying, Jinfa; Shen, Yang; Hummer, Gerhard; Bax, Ad
Abstract α‐Synuclein is an intrinsically disordered protein of 140 residues that switches to an α‐helical conformation upon binding phospholipid membranes. We characterize its residue‐specific backbone structure in free solution with a novel maximum entropy procedure that integrates an extensive set of NMR data. These data include intraresidue and sequential HNHα and HNHN NOEs, values for 3JHNHα, 1JHαCα, 2JCαN, and 1JCαN, as well as chemical shifts of 15N, 13Cα, and 13C′ nuclei, which are sensitive to backbone torsion angles. Distributions of these torsion angles were identified that yield best agreement to the experimental data, while using an entropy term to minimize the deviation from statistical distributions seen in a large protein coil library. Results indicate that although at the individual residue level considerable deviations from the coil library distribution are seen, on average the fitted distributions agree fairly well with this library, yielding a moderate population (20–30%) of the PPII region and a somewhat higher population of the potentially aggregation‐prone β region (20–40%) than seen in the database. A generally lower population of the αR region (10–20%) is found. Analysis of 1H1H NOE data required consideration of the considerable backbone diffusion anisotropy of a disordered protein.